What factors predict the engagement of dropouts in alternative secondary schools in Chile?. (March 2020) - Espinoza, Oscar; González, Luis Eduardo; McGinn, Noel; Castillo, Dante
Improvement in education has been one of the strategies of the government of Chile to reduce economic inequality. To that end, it recently established a system of Second Opportunity Centers that enroll out-of-school youth who have not completed high school. The system is modeled on so-called alternative schools operating in Europe and the United States. This study reports results on the first survey of students. Questionnaires were completed by a representative sample of 1112 students, drawn from 18 of the Ministry of Education's 134 Centers. Most of the respondents expressed satisfaction with their program, but there were significant differences between boys and girls, and across centers. Differences are explained by program activities in which students are engaged. Male students were more likely to have dropped out of regular high school because of academic difficulties; they are more likely to be engaged in the centers' sports activities. Girls were more likely to have left their school because of a family situation. They are more engaged in the centers' academic activities. The findings suggest how the centers' program could be made more effective in retaining students to graduation.